Segmentacja psychograficzna jako metoda badań marketingowych - Wanat, Tomasz (Wydział Prawa i Administracji UAM, 1994)
The article presents the results of research on market segmentation. Their essence consisted in the use of psychographic criteria, i.e. criteria relating to psychological properties affecting conconsumer behaviour. A sample of 300 inhabitants of Poznań were used in the research. Data collected with the use of questionna ires were first processed with factor analysis allowing to limit the number of variables, and then clustering analysis allowing to create certain groups. 6 such groups, called segments were distinguished: t he active, conservatives, townspeople, t he passive, aspiration- holders, and traditionalists. Each of the segments is characterized by a different lifestyle, and consequently, a different approach to shopping.
Psychographic segmentation as a method of marketing research